All eyes on Rafah: Kisah di balik sorotan dunia - Haq, Aula Fahimatul (Maliki Interdisciplinary Journal, 2024)
The recent events in Rafah require us to open our eyes to voice the rights of the Palestinian people. Living in fear and alertness of missiles sent by Israel can happen at any time. Hunger, cold, death have become their daily meals, as if the world is just watching their lives, the largest organization in the world, the United Nations, which fights for human rights, can only give warnings and condemnations and is only considered a passing wind by Israel. Then who can stop this genocide. Some efforts have been made as much as possible by all civilians in the world. This research method uses a qualitative approach. This research aims to provide information on what has happened in Palestine and also the efforts that have been made to stop this conflict.